SURG-27. TREATING HYDROCEPHALUS IN DIFFUSE MIDLINE GLIOMAS WITH AN H3 K27M MUTATION. (9th November 2020) - Coombs, L; LaRocca, R; Hata, Jessica; Nickols, H; Spalding, A; Mutchnick, Ian; Moriarity, Thomas; Gump, William; Sun, D
Abstract: BACKGROUND: Diffuse midline gliomas (DMG) are a subset of malignant gliomas that share a characteristic Histone H3K27M mutation. These tumors are centrally located and may cause hydrocephalus on initial presentation. DMG lack characteristic imaging that distinguish from other primary brain tumors in the midline. We conducted this retrospective chart review of 43 consecutive patients presenting with midline tumors to determine: how many had a DMG; whether DMG patients with hydrocephalus were candidates for resection; and what the outcomes of endoscopic third ventriculostomy (ETV) versus ventriculoperitoneal shunt (VPS) placement were, as compared to wild type (WT) tumors. METHODS: We conducted an IRB approved retrospective chart review of patients presenting with midline tumors from 9/2016-3/2020 to determine H3K27M mutation status, hydrocephalus, and neurosurgery intervention. RESULTS: The median age of all midline tumor patients was 19.1 years (range 1.1-80.1). 26% (11/43) of midline tumors presented with H3K27M mutation, with a higher rate of hydrocephalus compared to patients without mutation [7/11 (65%) for DMG vs. 6/32 (19%) for WT, p< 0.05]. Of the seven H3K27M patients presenting with hydrocephalus, none were candidates for resection, 5 underwent ETV, and 2 underwent VPS placement as initial management. 4 out of these 5 ETVs failed within an average of 24 days (6-42 days). 2 patients then underwent VP shunt placement; the other 2 underwent secondary ETV but both failed and required VP shunting as well. All 6 WT tumor patients had one procedure (1 ETV, 5 resection) to relieve hydrocephalus, and no patients had recurrent hydrocephalus. CONCLUSIONS: Both pediatric and adult patients may present with DMG associated with a higher rate of unresectable tumors and hydrocephalus on presentation. Furthermore, these data suggest that neuroendoscopic third ventriculostomy and septum pellucidum fenestration for the management of obstructive hydrocephalus in patients with DMG may be less robust than shunting.